Engaging African American Youth in the Development of a Serious Mobile Game for Sexual Health Education: Mixed Methods Study - Patchen, Loral; Ellis, Lindsey; Ma, Tony Xuyen; Ott, Corilyn; Chang, Katie H K; Araya, Brook; Atreyapurapu, Sravanthi; Alyusuf, Amal; Gaines Lanzi, Robin (JMIR Publications, 2020)
BackgroundAlthough teen pregnancy rates decreased dramatically in the United States over the past decade, the rates of sexually transmitted infections (STIs) among adolescents and young adults increased. STI rates disproportionately affect African American youth and young adults. Innovative, accessible, and culturally relevant sexual health interventions are urgently needed. ObjectiveThis study aimed to identify the optimal modality for a game-based sexual health intervention; develop the educational, entertainment, and technological aspects of the serious game; and demonstrate its usability and acceptance by the target population. MethodsThis project was grounded in formative data collection with community-based participatory research principles and practices combined with a user-centered design and development approach. Sexually Active Adolescent-Focused Education (SAAFE) was developed using input and feedback from African American youths aged 15 to 21 years who participated in a youth advisory board and focus group discussions to inform the co-design and cocreation of the serious game. The process was highly iterative with multiple sessions for user input following design changes. It proceeded in 3 stages. Social cognitive theory and problem-solving theory were leveraged to provide evidence-based, trauma-informed education through a serious game. Usability testing assessed the quality of user experience with the prototype. ResultsAcross all 3 stages, a total of 86 self-identified African American males and females aged 15 to 21 years from the District of Columbia and Birmingham, Alabama, participated. Participants requested a dating simulation game. They wanted SAAFE to be customizable, realistic, entertaining, educational, modern, and experiential, linking consequences to their gameplay decisions. Usability testing resulted in an initial System Usability Survey score of 77.7, placing the game in the 82nd percentile and above average for usability. ConclusionsInitial results suggest that the SAAFE prototype is a promising intervention to engage African American youth in sexual health education using a role-playing game. If proven efficacious, the game has the potential to meet the need for sex education, counterbalance unhealthy portrayals of sex in popular media, and respond to the disparities in the STI epidemic.